The Effect of a Parental Participation in Child Care Program on Anxiety and the Parental Role at a Pediatric Intensive Care Unit - Kaewvichit, Namtip; Thajeen, Kallayanee; Chantaramanee, Pranee; Chotsuwansiri, Tapanit (Princess of Naradhiwas University Journal, 2019)
The purposes of this quasi-experimental study (pretest-posttest control group design) were to examine the effects of parental participation into a child care program on their level of anxiety and parenting roles at a pediatric intensive care unit. Purposive sample was 50 parents of children who had been on endotracheal tubes and respirators, being admitted at the Songklanagarind Hospital between October 2016 and April 2017. Participants were assigned into one experimental and one control group (25 in each). Samples from experimental group received a parental participative child care program. Those in control group received routine care. Research instruments for data collection were questionnaires, including: 1) demographic data, 2) the State Anxiety Inventory Form Y-1 (Thai version) used to assess parental anxiety, and 3) the index of the parental roles. Content validity of the research tools was validated by three experts. Reliability of the questionnaires (The State Anxiety Inventory Form Y-1, and the index of parental role) was tested using Cronbach’s alpha coefficient, yielding values of .85 and .82, respectively. Data were analyzed by using independent t-test, as well as an analysis of covariance with pre-test anxiety score as a covariate The results showed that 48 hours after admission, parental anxiety mean score in the experimental group was significantly lower than in the control group (p < .01). Parental role mean score in the experimental group, measured 72 hours after the admission, was also significantly higher than in the control group (p < .01). This study concluded that a parental participation in child care program could reduce parental anxiety, and increase the parental roles at a pediatric intensive care unit. Therefore, provision of the parentalparticipation in child care program should be encouraged as a routine nursing practice.